Correlation between immunoexpression of BCL-2 protein family with apoptosis index, cellular proliferation and survival in colorectal carcinomas - Costa, Henrique de Olivira; Lima, Flávio de Oliveira [UNESP]; Barrazueta, Luis M.; Oshima, Celina; Silva Júnior, Jose Antonio da; Gomes, Thiago Simão; Artigiani Neto, Ricardo; Franco, Marcello (My University, 2012)
Objectives: To evaluate the Bcl-2, Bax, Bad and Bak immunoexpression in tumor and nontumorous tissue of 130 patients with colorectal carcinoma submitted to surgery at São Paulo Hospital, EPM/ UNIFESP, from 2002 to 2005, and to correlate the immunoexpression data with the apoptotic index (AI, obtained by anti-cleaved caspase 3 and M30 labeling), cell proliferation score (CPS, obtained by Ki-67), immunoexpression of p53 and patient’s clinical prognosis. Results: Positive correlation was verified between Bcl-2 protein family in tumor and nontumor tissue. Only Bcl-2 protein correlated with IA and CPS in the tumor. Positive correlation was observed between pro- -apoptotic proteins and Bcl-2 protein. In the adjacent mucosa, Bcl-2 correlated with Ki-67 and p53, but not with IA. Carcinomas exhibited higher immunoexpression of CPS and IA markers. No correlation occurred between immunoexpression data and patient survival. Conclusion: Positive correlation was observed between the pro-apoptotic proteins of the Bcl-2 family and the anti-apoptotic protein Bcl-2. In the adjacent nontumor mucosa, Bcl-2 correlated with Ki-67 and p53, but not with AI. Carcinomas presented greater immunoexpression for CPS and AI markers; however immunoexpression of these markers was not correlated with patient survival.
Keywords: Apoptosis; c bcl 2 proteins; Cell proliferation; Colorectal neoplasms; Microarray analysis